Neo-Ahl Al-Hadîts In Contemporary Islamic Legal Thought: The Influence of Nâshir al-Dîn al-Albânî in the Salafist Movement in Indonesia - Faizin, Afwan (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
Nâshîr al-Dîn al-Albânî is one of the most influential figure in the contemporary Salafist movement, alongside Bin Bâz and Uthaymin. This article will discuss the influence of Nasir al-Din al-Albâni on Indonesian Salafi Islamic legal thought. In the discourse of Islamic legal thought in Indonesia, some scholars explain the importance of al-Albânî's role in defending Ibn Bâz's fatwas by writing dozens of works, including his fatwas, that have been translated into Indonesian. On the other hand, other scholars emphasized al-Albânî's central role in the global Salafist movement as a contemporary Salafist ideologue. This figure calls for ijtihad based on authentic traditions and rejects tackled and bequeaths his brand of Salafism in deconstructing the traditions of schools of fiqh. The research question is what is the influence of al-Albânî's takhrîj traditions on Indonesian Salafist Islamic legal thought? This is qualitative research with a historical, hadith scientific, and sociological approach. The findings of this study are that the traditions of takhrîj al-Albânî and its understanding have led to the strengthening of a strict literal way of Islamic law. Al-Albâni greatly influenced Indonesian Salafists in forming a pattern of thought called